Вплив організаційно-технологічних умов на ефективність процесу виконання робіт житлового будівництва - Ушацький, С. А.; Шатрова, І. А.; Шатров, С. В. (Ways to Improve Construction Efficiency, 2012)
The questions of article contains an analysis of how the effectivity of process of building of blocks of flats depends on the technological and managing conditions. The analysis was made by using the theory of mass service.